Effect of Passive Hyperthermia on Working Memory Resources during Simple and Complex Cognitive Tasks - Gaoua, Nadia; Herrera, Christopher P.; Périard, Julien D.; El Massioui, Farid; Racinais, Sebastien (Frontiers in Psychology, 2018)
The aim of this study was to verify the hypothesis that hyperthermia represents a cognitive load limiting available resources for executing concurrent cognitive tasks. Electroencephalographic activity (EEG: alpha and theta power) was obtained in 10 hyperthermic participants in HOT (50°C, 50% RH) conditions and in a normothermic state in CON (25°C, 50% RH) conditions in counterbalanced order. In each trial, EEG was measured over the frontal lobe prior to task engagement in each condition (PRE) and during simple (OTS-4) and complex (OTS-6) cognitive tasks. Core (39.5 ± 0.5 vs. 36.9 ± 0.2ºC) and mean skin (39.06 ± 0.3 vs. 31.6 ± 0.6ºC) temperatures were significantly higher in HOT than CON (P<0.005). Theta power significantly increased with task demand (p=0.017, η2=0.36) and was significantly higher in HOT than CON (p=0.041, η2=0.39). The difference between HOT and CON was large (η2=0.40) and significant (p=0.036) PRE, large (η2=0.20) but not significant (p=0.17) during OTS-4, and disappeared during OTS-6 (p=0.87, η2=0.00). Those changes in theta power suggest that hyperthermia may act as an additional cognitive load. However, this load disappeared during OTS-6 together with an impaired performance, suggesting a potential saturation of the available resources.